Causal relationship between iron deficiency anemia and asthma: a Mendelian randomization study - Li, Mengchun; Chen, Zhengdong; Yang, Xin; Li, Wanwei (Frontiers in Pediatrics, 2024)
Background:Observational studies have suggested an association between iron deficiency anemia (IDA) and asthma, which may affect the occurrence of asthma.However, whether IDA is a new management goal for asthma remains to be determined.Objective:We conducted a two-sample Mendelian randomization(MR)analysis to assess the association between IDA and asthma.Methods:We performed a two-sample MR study to assess a causal relationship between IDA(ncase=12434,ncontrol=59827)and asthma(ncase=20629,ncontrol=135449).Inverse variance weighted (IVW) was used as the primary method for the analyses.Furthermore, we used weighted medians and MR-Egger to enhance robustness.Data linking genetic variation to IDA and asthma were combined to assess the impact of IDA on asthma risk.Results:There are five single nucleotide polymorphisms (SNPs) were used as genetic tool variables for exposure factors.Genetically determined IDA was significantly associated with an increased risk of asthma(OR=1.37,95%CI:1.09-1.72,p=0.007).There was little heterogeneity in the MR studies and no evidence of level pleiotropy was found.Conclusions:In our MR study, our findings emphasize that IDA may be associated with a high risk of asthma, indicating a potential role for IDA in the development of asthma.Future research needs to elucidate its potential mechanisms to pave the way for the prevention and treatment of asthma.